Determination of ultra-trace levels of metal ions in sea-water with on-line preconcentration and electrothermal atomic absorption spectrometry - PORTA, Valerio; ABOLLINO, Ornella; MENTASTI, Edoardo; SARZANINI, Corrado (1991)
An on-line pre-concentration system for electrothermal atomic absorption spectrometry was developed. A miniature silica C-18 column was inserted at the tip of the autosampler arm. A modification of the tubing line of the autosampler allowed either the flow of the sample through the column or the operation of the autosampler in the normal mode. The retention of the metal ions in the form of complexes on the microcolumn was achieved by using pyrrolidin-l-yl dithioformate as the complexing agent; acetonitrile was then used for the elution. The direct injection of the eluate into the graphite furnace gave high pre-concentration factors, ranging between 20 and 225, which are sufficient for the determination of Cd, Pb, Cu, Ni, Co and Fe in Antarctic sea-water. The blank level was very low and the detection limits ranged from 0.4 ng l-1 (Cd) to 25 ng l-1 (Fe).